Processing of Heavy Crude Oils - Challenges and Opportunities 2019
DOI: 10.5772/intechopen.89486
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Treatment of Heavy Crude Oils for Refining

Abstract: The economic unattractiveness of heavy crude oils in the global oil market scene is fast changing due to the looming scarcity of light oils. There are huge reserves of heavy oils to which refiners are being reluctantly attracted. The fully developed conventionally available refineries are, however, incapable of processing these heavy crudes without some major modifications of both process and equipment, which will be capital intensive. This thrust promises to be very viable and yield great benefits since heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The negative effects of heavy metals include equipment fouling and corrosion due to chloride salts and catalyst deactivation. 96 It was pointed out that the separation of mineral matter from the bitumen is challenging. It is preferable not to have metals in bitumen.…”
Section: Cavitation-assisted Demetallization Of Bitumenmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative effects of heavy metals include equipment fouling and corrosion due to chloride salts and catalyst deactivation. 96 It was pointed out that the separation of mineral matter from the bitumen is challenging. It is preferable not to have metals in bitumen.…”
Section: Cavitation-assisted Demetallization Of Bitumenmentioning
confidence: 99%
“…The most abundant metals found in mineral-free bitumen were Al, Fe, K, Na, Ni, Ti, and V. Several case studies have reported that heavy metals in bitumen have adverse effects on the refining equipment and processes. The negative effects of heavy metals include equipment fouling and corrosion due to chloride salts and catalyst deactivation . It was pointed out that the separation of mineral matter from the bitumen is challenging.…”
Section: Cavitationally Driven Transformations In Bitumen Processingmentioning
confidence: 99%
“…In some cases, de-emulsiers may be added to further break emulsions (sometimes referred to as chemical desalting). 39,44,[46][47][48] Other approaches studied for breaking emulsions in crude oil include the use of ultrasonic elds, microwave radiation (thermal), cyclonic separation, and membranes. 43,[49][50][51][52][53][54][55][56][57][58][59] The salt-and solid-containing aqueous stream may be subjected to a stripping process to remove hydrogen sulde and benzene.…”
Section: Summary Of the Crude Oil Desalting Processmentioning
confidence: 99%
“…[ 87 ] b)Some nanoparticles' toxicity and their effects on humans, pollution, and environmental sustainability are debated. [ 95 ] c)Formation heterogeneity could impair nanoparticles' overall effectiveness in the porous medium. [ 96 ] d)There is a current absence of explicit normalized models for assessing nanomaterial execution in different applications (e.g., partitioning oil or water beads and emulsion destabilization).…”
Section: Challenges To Using Nanomaterialsmentioning
confidence: 99%